Perceived deception: Evaluating source credibility and self-efficacy. Issue 4 (1st October 2016) - Ormond, Dustin; Warkentin, Merrill; Johnston, Allen C.; Thompson, Samuel C.
ABSTRACT: Detecting scareware messages that seek to deceive users with fear-inducing words and images is critical to protect users from sharing their identity information, money, and/or time with bad actors. Through a scenario-based experiment, the present study evaluated factors that aid users in perceiving deceptive communications. An online experiment was administered yielding 213 usable responses. The data from the study indicate high levels of deception detection self-efficacy and source trustworthiness increase the likelihood an individual will perceive a scareware message as deceptive. Additionally, technology awareness enhances self-efficacy to detect deception and reduces individual perceptions of source trustworthiness. Finally, the data significantly illustrate behavioral intention to use scareware is lower when the message is perceived as deceptive.